2012
DOI: 10.1021/jo302033f
|View full text |Cite
|
Sign up to set email alerts
|

Triazolyl Donor/Acceptor Chromophore Decorated Unnatural Nucleosides and Oligonucleotides with Duplex Stability Comparable to That of a Natural Adenine/Thymine Pair

Abstract: We report the design and synthesis of triazolyl donor/acceptor unnatural nucleosides via click chemistry and studies on the duplex stabilization of DNA containing two such new nucleosides. The observed duplex stabilization among the self-pair/heteropair has been found to be comparable to that of a natural A/T pair. Our observations on the comparable duplex stabilization has been explained on the basis of possible π-π stacking and/or charge transfer interactions between the pairing partners. The evidence of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 110 publications
0
24
0
Order By: Relevance
“…Thus, the β‐configuration was established via NOESY spectra of FTPhen nucleoside which showed a cross peak between H1′ ‐ H2′α and H1′ ‐ H4′. The β‐anomeric configuration was further confirmed from X‐ray single crystal structure analysis (Figure ) . The X‐ray single crystal analysis revealed that the unit cell of the fused triazolylphenanthrene nucleoside, FTPhen , contained four molecules with one H 2 O in the unit cell with space group P1, cell length, a=7.19, b=10.86, c=20.87 A; cell angles a=82.43, b=88.57, g=84.36 o and cell volume 1608.7 (Figure a‐b).…”
Section: Figurementioning
confidence: 80%
See 4 more Smart Citations
“…Thus, the β‐configuration was established via NOESY spectra of FTPhen nucleoside which showed a cross peak between H1′ ‐ H2′α and H1′ ‐ H4′. The β‐anomeric configuration was further confirmed from X‐ray single crystal structure analysis (Figure ) . The X‐ray single crystal analysis revealed that the unit cell of the fused triazolylphenanthrene nucleoside, FTPhen , contained four molecules with one H 2 O in the unit cell with space group P1, cell length, a=7.19, b=10.86, c=20.87 A; cell angles a=82.43, b=88.57, g=84.36 o and cell volume 1608.7 (Figure a‐b).…”
Section: Figurementioning
confidence: 80%
“…Electrostatic potentials mapped as colors on the surfaces showed its hydrophobic character with negative charge density onto the triazole ring indicating significantly less polar nucleoside. The triazolylphenanthrene unit in FTPhen is fully planar in contrary to our earlier reported base TPhen B Do . As the stacking propensity is the reflection of surface area and hydrophobicity of DNA bases and analogues, we calculated these parameters for FTPhen nucleoside .…”
Section: Figurementioning
confidence: 97%
See 3 more Smart Citations